2017
DOI: 10.3310/pgfar05180
|View full text |Cite
|
Sign up to set email alerts
|

Implications for a policy of initiating antiretroviral therapy in people diagnosed with human immunodeficiency virus: the CAPRA research programme

Abstract: BackgroundMore than 100,000 people in the UK are living with a human immunodeficiency virus (HIV) infection. There are currently estimated to be around 4000 people newly infected in the UK per year, mostly men who have sex with men (MSM). It has become increasingly clear that antiretroviral therapy (ART) used to treat people infected with HIV also has a profound effect on infectivity. At the initiation of the programme, it was the policy in the UK to initiate ART in people when their cluster of differentiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…However, we note that HIV incidence may be underreported in this study, taking into account the significant loss to follow-up reported among the couples who declined preconception. Nevertheless, this study demonstrates a decrease in HIV acquisition as a result of HAART, comparable to results from clinical trials among [13,16,17].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, we note that HIV incidence may be underreported in this study, taking into account the significant loss to follow-up reported among the couples who declined preconception. Nevertheless, this study demonstrates a decrease in HIV acquisition as a result of HAART, comparable to results from clinical trials among [13,16,17].…”
Section: Discussionsupporting
confidence: 81%
“…ere is existing data that PLWHIV who are adherent to highly active antiretroviral therapy (HAART) and maintaining an undetectable viral load have effectively no risk of sexually transmitting HIV [7,[13][14][15]. A 96% reduction in HIV transmission among discordant couples [13] even in the presence of inconsistent condom use [16] and over long periods (up to 10 years) has been reported. Moreover, maternal viral suppression to undetectable levels before conception, during pregnancy, and at the time of delivery makes perinatal HIV transmission almost entirely preventable [17,18].…”
Section: Introductionmentioning
confidence: 99%